2013
DOI: 10.1002/chem.201203867
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Synthesis and Photophysical and Electrochemical Studies of 20‐Substituted Cyanine Dye–Purpurinimide Conjugates: Incorporation of NiII into the Conjugate Enhances its Tumor‐Uptake and Fluorescence‐Imaging Ability

Abstract: We report herein a simple and efficient approach to the synthesis of a variety of meso-substituted purpurinimides. The reaction of meso-substituted purpurinimide with N-bromosuccinimide regioselectively introduced a bromo functionality at the 20-position, which on further reaction with a variety of boronic acids under Suzuki reaction conditions yielded the corresponding meso-substituted analogues. Interestingly, the free base and the metalated analogues showed remarkable differences in photosensitizing efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…We selected Pd(OAc) 2 as the palladium catalyst of choice for further investigation because of its high catalytic activity and low cost. A brief investigation of solvents found that ethereal solvents, such as THF and dioxane, were suitable reaction media (entries [14][15][16][17]. Among which, THF was the solvent of choice in terms of yield of the desired fluorinated product Zn-2a (entry 14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected Pd(OAc) 2 as the palladium catalyst of choice for further investigation because of its high catalytic activity and low cost. A brief investigation of solvents found that ethereal solvents, such as THF and dioxane, were suitable reaction media (entries [14][15][16][17]. Among which, THF was the solvent of choice in terms of yield of the desired fluorinated product Zn-2a (entry 14).…”
Section: Resultsmentioning
confidence: 99%
“…The construction of porphyrins and related tetrapyrrolic macrocycles has attracted much interest [1][2][3][4][5][6] because they have a variety of important applications in many fields [7,8], including catalysis [9][10][11][12][13][14], medicine [15][16][17][18], and materials [19][20][21][22][23][24][25][26][27]. It is also well documented that the chemical, physical, and biological properties of porphyrin macrocycles can be systematically tuned by the electronic, steric and conformational environments of their peripheral substituents [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate a broader applicability of the iEDDA approach, the as‐synthesized gold NP has also been conjugated with a tetrazine‐cyanine: 6‐methyl‐tetrazine‐sulfo‐Cy5 (TzCy5) near‐infrared dye. Indeed, cyanine 5 (Cy5) is a bright, near‐infrared (NIR) fluorescent probe currently used for biological imaging due to the low autofluorescence of biological specimens in this region of the spectrum . After removal of excess dye by a drastic washing using ultrafiltration units with a saline solution, the effective coupling of TzCy5 onto the nanoparticle surface was assessed by UV/Vis and fluorescence spectroscopies (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, cyanine 5( Cy5) is ab right, near-infrared (NIR) fluorescent probe currently used for biological imaging due to the low autofluorescence of biological specimens in this region of the spectrum. [55][56][57] After removalo f excessd ye by ad rastic washing using ultrafiltration units with as aline solution, the effective coupling of TzCy5 onto the nanoparticle surface was assessed by UV/Vis and fluorescence spectroscopies ( Figure 5). The excitation spectrum (Figure 5a, solid lines) showst hat TzCy5 coupled Au@HMBPene NPs exhibit ap eak at 648 nm, which is in good agreement with the excitation (solid line) and the UV/Vis absorption (Figure 5a,c ircles) spectra from the free TzCy5.…”
mentioning
confidence: 99%
“…Later, the same and other groups synthesized and evaluated spectroscopic properties of the range of dyads consisting of chlorin as a donor and DOTA-chelated elements (Nd, Yb, Pd, Cu) as an acceptor. Ethirajan and colleagues conjugated cyanine acceptor with metallochlorin donors. The researchers observed both cyanine fluorescence after irradiation of Ni-chlorin and improved dyad photostability due to singlet oxygen decomposition by Ni-chlorin . Lovell and coauthors developed new “on-line” caspase-responsive FRET system based on 5-carboxy-X-rhodamine donor and pyropheophorbide acceptor for fluorescence guiding feedback-oriented PDT and monitoring cancer cell death .…”
Section: Visualizationmentioning
confidence: 99%